2015
DOI: 10.1371/journal.pone.0127055
|View full text |Cite
|
Sign up to set email alerts
|

Mistletoe Infection in an Oak Forest Is Influenced by Competition and Host Size

Abstract: Host size and distance from an infected plant have been previously found to affect mistletoe occurrence in woody vegetation but the effect of host plant competition on mistletoe infection has not been empirically tested. For an individual tree, increasing competition from neighbouring trees decreases its resource availability, and resource availability is also known to affect the establishment of mistletoes on host trees. Therefore, competition is likely to affect mistletoe infection but evidence for such a me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 34 publications
1
20
0
1
Order By: Relevance
“…infection include reduced tree vitality, shoot die-off, and reduction of the quality and volume of wood produced (Figure 1). The influence of common mistletoe (Viscum album L.) on deciduous trees, especially along roadsides, in parks, and in plantations, has been well studied for years [1][2][3]. According to Barney et al [4], mistletoe colonizes over 450 species and varieties of trees.…”
Section: Is Mistletoe a Problem In The Forests?mentioning
confidence: 99%
“…infection include reduced tree vitality, shoot die-off, and reduction of the quality and volume of wood produced (Figure 1). The influence of common mistletoe (Viscum album L.) on deciduous trees, especially along roadsides, in parks, and in plantations, has been well studied for years [1][2][3]. According to Barney et al [4], mistletoe colonizes over 450 species and varieties of trees.…”
Section: Is Mistletoe a Problem In The Forests?mentioning
confidence: 99%
“…The number of mistletoe seeds are usually limited, so the decrease in the probability of mistletoe infection with an increase in competition from neighboring hosts may arise not from changes in resource availability but simply from a decreasing probability of receiving mistletoe seeds due to increased number of neighboring host. Matula et al (2015) found the same mechanism, that competition among host has a negative effect on occurrence of the mistletoe, Loranthus europaeus , in an oak forest in the Czech Republic.…”
Section: Discussionmentioning
confidence: 84%
“…Kuijt, Santales: Loranthaceae) es una planta arbustiva que parasita los brotes aéreos de los hospederos; son organismos que pueden fotosintetizar, es decir, solo obtienen nutrientes minerales y agua del huésped (Mathiasen et al 2008). Tienen un papel importante en el mantenimiento de la diversidad forestal al proporcionar recursos alimentarios claves para muchas especies animales debido a la disponibilidad de su fruto en épocas en que otros alimentos son escasos (Matula et al 2015). Los efectos estudiados en el muérdago varían en función no solo de su capacidad de tomar agua y nutrientes del árbol hospedante, sino, también, dependen de las condiciones ambientales en las que se desarrolla el anfitrión, su tamaño, edad y densidad.…”
Section: Modelación De La Distribución Espacial Del Muérdago (Santalaunclassified